DIVERSITY OF SPECIES CRUSTOSE LICHEN OF Plumeria spp. IN BALI ISLAND - Hardini, Junita; Kasiamdari, Rina Sri; Santosa, Santosa; Purnomo, Purnomo (Metamorfosa: Journal of Biological Sciences, 2018)
The research of species crustose lichen was conducted in the lowlands of the Bali Island and  was  conducted  randomly at a height of 0-500 m  above  sea  level. The aim is to find out the diversity of species crustose lichen living in  Plumeria  spp. The method used is descriptive  qualitative  analysis  method. Data  collection  was  done  by field observation and specimen collection. The lichen specimens were observed and identified morphologically, anatomically, and chemically. In this study found of four families consisting of six genera and 15 species, namely Graphina  sp., Phaeographina  sp., Graphis sp., Graphis immersella , G. nilgiriensis, G. modesta, G. nana, and G. conferta   (Graphidaceae); Lecanora sp.1, and Lecanora sp.2 (Lecanoraceae);  Lepraria sp. (Stereocaulaceae);  Caloplaca sp. (Teloschistaceae). The most common species is  Graphis  sp. (88%).